Data related to the manufacturing and mechanical performance of 3D-printed metal honeycombs - Afkhami Shahriar; Amraei Mohsen; Poutiainen Ilkka; Gardner Leroy; Piili Heidi; Wadee M. Ahmer; Salminen Antti; Björk Timo (Elsevier BV, 2025)
The data available in this article include 3D mechanical designs used for the computer-aided fabrication of metal honeycombs produced by additive manufacturing and studied in [1]. In addition, the force-displacement data utilized to evaluate the mechanical performance of the metal used in this study are available via the digital image correlation technique. Further, the surface features obtained using 3D scanning microscopy of the fabricated parts are available as raw files and processed data. Finally, the impact test data are presented as high-frame-rate videos showing the time-displacement numerical values. This information has been provided in this data article to complement the related research, serve as a guide for future studies, and ensure the data's repeatability and reliability of the related research paper. The research article [1] investigates the mechanical performance and failure mechanism of additively manufactured metallic honeycombs under various scenarios, from quasi-static to dynamic loading. It also investigates the design optimization of these energy-absorbing hollow structures by comparing hollow structures made of three distinct novel cell designs (triangular, diamond-shaped, and diamond-shaped with curved walls) with traditional honeycombs made of hexagonal cells.